2015
DOI: 10.1007/s13364-015-0215-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing variables as predictors of habitat suitability of the viscacha rat (Octomys mimax), a rock-dwelling mammal living in a desert environment

Abstract: Identifying high-quality habitats across large areas is a central goal in biodiversity conservation. Remotely sensed data provide the opportunity to study different habitat characteristics (e.g., landscape topography, soil, vegetation cover, climatic factors) that are difficult to identify at high spatial and temporal resolution on the basis of field studies. Our goal was to evaluate the applicability of remotely sensed information as a potential tool for modeling habitat suitability of the viscacha rat (Octom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The mean texture of BI was lower on occurrence points than on absence points because low mean values indicate less bright areas, such as the rocky substratum (Campos et al. ), where this species occurs. Variance was also included in the best model; this measure is ecologically relevant since it captures textural heterogeneity (Wood et al.…”
Section: Discussionmentioning
confidence: 98%
“…The mean texture of BI was lower on occurrence points than on absence points because low mean values indicate less bright areas, such as the rocky substratum (Campos et al. ), where this species occurs. Variance was also included in the best model; this measure is ecologically relevant since it captures textural heterogeneity (Wood et al.…”
Section: Discussionmentioning
confidence: 98%
“…To potentially extend their habitat to neighboring areas, we proposed a habitat suitability prediction method based on noninvasive field observations from remote sensing imaginh using a UAS multispectral camera system and machine learning classification. Since the evaluated environmental conditions, including vegetation, soil, and topography criteria, impact the ecological gradient of both flora and fauna species [50][51][52], the proposed approach should be applicable to a wide variety of endangered species. Moreover, the application of the UAS mounted multispectral camera system ensured that flora and fauna species would be minimally disturbed in their natural habitat during the field observations and non-invasive population count [53].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the specific impact of forest structure on small mammal diversity and less still on how LiDAR measurements of forest structure relate to the life history requirements of multiples species of small mammals [12,62]. Thus, we analyzed the ability of few specific variables that encompass a wide range of forest structural attributes to predict small mammal diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The few prior studies on remotely-sensed habitat suitability for small mammals have found LiDAR effectively predicts small mammal habitat use. However, these studies are focused on abundance and habitat use of single species, rather than overall small mammal community diversity [11][12][13]. Small mammals crucially contribute to ecosystem function through their roles in seed propagation, organic matter decomposition, and soil mixing [14][15][16].…”
Section: Introductionmentioning
confidence: 99%